Vitamin D supplementation at different doses affects the vagal component of the baroreceptor reflex and the Bezold-Jarisch reflex in eutrophic rats - Fioretti, Alexandre C.; Dsouki, Nuha A.; do Vale, Barbara; de Carvalho, Rodrigo P.; Dias, Daniel P. M.; Venancio, Daniel P.; Fonseca, Fernando L. A.; Sato, Monica A. (Frontiers in Physiology, 2022)
Vitamin D has been used to prevent several diseases. The 1,25 (OH) 2D3, the active form of vitamin D (VitD), participates in calcium metabolism, and has direct action in various tissues as those of the cardiovascular system binding to the VitD receptor. We investigated whether the supplementation with different doses of VitD affect or not the resting mean arterial pressure (MAP) and heart rate (HR), heart rate variability (HRV), baroreceptor and Bezold-Jarisch reflexes in eutrophic rats. Adult male Wistar rats were randomly assigned in 4 groups (Control, VitD 15, 250, and 3,750 IU/day, n = 6/group). After 3 days of supplementation, MAP and HR recordings were performed in freely moving rats. Baseline (resting) MAP, HR, and HRV showed no difference in Control and VitD groups. Nevertheless, the index of the baroreceptor reflex showed that the bradycardic component of the baroreflex evoked by a pressor dose of phenylephrine (3 μg/kg of b.w.) in bolus injection had a significant increase in rats supplemented with VitD 15 IU/day for 3 days compared to Control animals. No difference was observed in the index of the baroreflex evaluated with phenylephrine in rats treated with VitD 250 and 3,750 IU/day for 3 days in comparison to the Control group. The index of the baroreceptor reflex evaluated with an intravenous bolus injection of a depressor dose of sodium nitroprusside (30 μg/kg of b.w.) showed that the tachycardic component of the baroreflex is not different comparing all groups supplemented with VitD and Control animals. Rats supplemented with VitD 15 IU/day presented exaggerated bradycardic responses to the intravenous injection of phenylbiguanide (PBG, 5 μg/kg of b.w.) compared to Control animals, despite the similar hypotension in both groups. Higher doses of supplementation of VitD (250 and 3,750 IU/day for 3 days) abolished the hypotension and bradycardia induced by PBG. The findings suggest that the supplementation with different doses of VitD (15, 250, and 3,750 IU/day) for 3 days did not affect the resting arterial pressure, heart rate and autonomic modulation on the heart in rats. Despite that, the supplementation with a low dose of VitD (15 IU/day for 3 days) improved the sensitivity of the bradycardic component of the baroreflex, whereas higher doses of supplementation with VitD (250 and 3,750 IU/day for 3 days) were unable to cause such effect. In addition, the Bezold-Jarisch reflex responses can be affected regardless the dose of VitD (15, 250 or 3,750 IU/day) supplementation for 3 days in rats.